Common use of standardized assessments by occupational therapists in the government setting in Malaysia/ Wan Nurulaini Wan Shafie and Kannan K Thanapalan - Wan Shafie, Wan Nurulaini; Thanapalan, Kannan K (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Use of standardized assessment (SA) tools reflects the Occupational Therapy (OT) domain of practice. The purpose of this study was to identify the common use, purposes and the perceptions of standardized assessments by Occupational Therapists in Malaysia. Online survey was conducted and the survey questionnaire consists of Part A (Demographic Questions) and Part B(Occupational Therapy Clinicians’ Use of Standardized Assessment Measures). With response rate of 22.6%, 64 respondents were analyzed. The Modified Barthel Index (MBI) was the most popular outcome measure. Most of the respondents reported they used the SA as the screening tools. As for the perceptions of SA, mostly the respondents have higher knowledge in selecting the appropriate measure and psychometric properties (validity and reliability). The respondents also agree that the most important factor in using the SA was the availability of the measures in their workplace. The usage of the SA by OTs in Malaysia needs to be improved to ensure the crediblity in OT practice.